(untitled) - Çengel, Yunus A. (Dubuque, IA, 2008)
Introduction to Thermodynamics and Heat Transfer provides balanced coverage of the basic concepts of thermodynamics and heat transfer.Together with the clear an numerous illustrations, student-friendly writing style, and manageable math, this is an ideal text for an introductory thermal science course for non-mechanical engineering majors.
Keywords: Thermodynamics,Nhiệt động lực học